House of Games - Katz, Jonathan; Jans, Alaric 1949- (<<The>> Criterion Coll., 2007)
A therapist and best-selling author must confront her own demons when she meets a man who has gambling debts and she feels compelled to help him.
Bildformat 1.78:1. - New, restored high-definition digital transfer, supervised by director of photography Juan Ruiz Anchía
Orig.: USA 1987
Enth. audio commentary by director David Mamet and consultant and actor Ricky Jay ; new video interviews with actors Lindsay Crouse and Joe Mantegna ; David Mamet on "House of games," a short documentary shot on location during the film's preparation and production ; storyboard detail ; theatrical trailer ; plus: an essay by critic Kent Jones and excperts from Mamet's introduction to the published screenplay
Keywords: Gamblers - Drama; Gambling - Drama; Swindlers and swindling - Drama; Women psychiatrists - Drama; Detective and mystery films.; Gamblers -- Drama; Gambling -- Drama; Swindlers and swindling -- Drama; Women psychiatrists -- Drama; Feature films; Fiction films; Thrillers (Motion pictures)